Musykilah Tarjamah al-Lughah al-Arabiyyah Ila al-Lughah al-Indonesiyyah - Aflisia, Noza (Sekolah Tinggi Agama Islam (STAIN)Curup, 2017)
The translation of Arabic into Indonesian is an important process because many of the sciences are written in Arabic from Islamic history, Islamic civilization, jurisprudence, ethics, even medicine, numerology, etc., all written in Arabic. The Arabic language has the advantages so that the higher language of the other language of its characteristic is in the field of audio, tandem, derivation, expression, verbal participation, and sculpture. Which is done in the translation work say in the translator. In order to be a good translator, he should be familiar with everyday vocabulary and vocabulary in both languages (Arabic and Indonesian). He should be familiar with the tools of influence and persuasion in both languages ââand how to use them and be familiar with the language and culture to which he translates. And that the translation should be written to the spoken language reader, even though the original text was not written for public reading, and is sincere in translating it and harnessing all its forces in it. In the structure of the Arabic sentence is often encountered sentence that makes it difficult for students to determine what is effective and the beginning and the action and the experience and the effect and complementary, in this writing parables by the translation of the actual sentence, the building of the known, and the building of the container, and, and, and, and,